Two Case Reports of Elastolytic Giant Cell Granuloma on the Palms - Promsena P; Triyangkulsri K; Rutnin S (Dove Medical Press, 2023)
Pichamon Promsena, Korn Triyangkulsri, Suthinee Rutnin Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Suthinee Rutnin, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211, Email suthinee.rutnin@gmail.comAbstract: Elastolytic giant cell granuloma (EGCG) is a rare granulomatous reaction hypothesized to occur because of the altered antigenicity of elastic fibers, resulting in cellular immunological reactions. The hallmarks of EGCG include elastolysis, elastophagocytosis, and multinucleated giant cell infiltrations. EGCG was first described as an actinic granuloma or annular elastolytic giant cell granuloma that classically presents as centrifugally expanding annular plaques on sun-exposed areas. It was recently named EGCG due to reports of non-annular lesions in various sun-protected areas. Hand involvement has been described but is almost exclusively confined to the dorsal and lateral aspects of the hands. Herein, we report two cases of EGCG on the palms, an unusual site of presentation, that were successfully treated with topical, high-potency corticosteroids. EGCG should be included in the differential diagnosis in cases of annular skin lesions located on the marginal area of the palms.Keywords: actinic granuloma, collagenous and elastotic marginal plaques of the hands, elastophagocytosis, granuloma annulare, paraneoplastic syndrome, autoimmunity